Asymmetric development of the nervous system - Alqadah, Amel (Dev Dyn, 2017)
The human nervous system consists of seemingly symmetric left and right halves. However, closer observation of the brain reveals anatomical and functional lateralization. Defects in brain asymmetry correlate with several neurological disorders, yet our understanding of the mechanisms used to establish lateralization in the human central nervous system is extremely limited. Here, we review left-right asymmetries within the nervous system of humans and several model organisms, including rodents, zebrafish, chickens, Xenopus, Drosophila, and the nematode Caenorhabditis elegans. Comparing and contrasting mechanisms used to develop left-right asymmetry in the nervous system can provide insight into how the human brain is lateralized.